Pre-enrichment step, incubation temperature and type of selective media affect the pathogenic Vibrio parahaemolyticus detection efficiency in frozen prawns - Sadeghi, Salima; Thong, Kwai Lin; Chai, Lay Ching (Springer International Publishing, 2019)
This study evaluates the performance of different detection protocols of Vibrio parahaemolyticus in frozen prawns. The effect of enrichment and incubation temperature on the selectivity of thiosulfate citrate bile sucrose (TCBS) and CHROMagar™ Vibrio (CAV) media were determined. Enumeration of V. parahaemolyticus in frozen prawns by direct-plating on CAV at 37 °C yielded the highest count compared to the other tested direct-plating protocols (p < 0.05). The enrichment step was found to increase the selectivity of TCBS for V. parahaemolyticus but did not affect the selectivity of CAV. Furthermore, trh + V. parahaemolyticus isolates were only successfully recovered from CAV, suggesting that CAV is the better media for the detection of virulent V. parahaemolyticus compared to TCBS. Repetitive Extragenic Palindromic PCR typing (REP-PCR) indicated that CAV and TCBS, as well as direct-plating or enrichment-plating are selective for different subsets of V. parahaemolyticus present in a sample. In conclusion, the current work suggests that CAV is a better selective media for detection and isolation of V. parahaemolyticus in frozen prawns. This study also suggests that direct-plating on CAV with an incubation temperature of 35–37 °C could be an alternative to Most Probable Number (MPN)-PCR for enumeration of V. parahaemolyticus in frozen prawn samples. © 2019, Bundesamt für Verbraucherschutz und Lebensmittelsicherheit (BVL).